¿Quién Estará a mi Lado? - Torres, Martin (Revista Universidad de Guayaquil, 1998)
When I die right now or at any momentWho will be by my side?It’s something I never, ever thought about,but today, just now, I think about it again,returning to the child’s soul, because only childrencan think this way when they love so muchwithout yet feeling the pain of life.Who will be by my side as long as I saythe final goodbye? That’s what I don’t know,we don’t know, it’s like guessing the lottery,or guessing if the dog we love will be there,and worse, if there will be love forever.The truth is, if there are some, one—or no one, we must be ready for the departureand love the loneliness that awaits us,the new loneliness that works miracles,like peacefully leaving for sweet sleep,that which awaits us, without hugs, or kisses,nor flowers or prayers, alone, alone, so alonewithout anyone’s face or any word,forever...